DEM simulation on packing densification of equal spheres under compression. (July 2014) - Wu, Y.; An, X.; Huang, F.
<x content-type="archive" xml:space="preserve">Abstract</x> The packing densification of mono-sized spheres under compression is numerically modelled and studied by using the discrete element method (DEM). The obtained macro packing property such as packing density and micro properties such as coordination number (CN), radial distribution function (RDF), angular distribution function (ADF), and pore structure (Voronoi/Delaunay tessellation) are characterised and compared with those properties of random loose packing (RLP) obtained under natural packing and random close packing (RCP) obtained under one-dimensional (1D) vibration. The results indicate that by properly controlling the pressure, the maximum random packing density of about 0·64 can be realised, implying that external compression is an effective way to realise the transition from RLP to RCP. Besides, the properties of RCP obtained under compression in this study are much comparable with that obtained under 1D vibration. The pushing filling mechanism of macro pores under compression was also identified by dynamic analysis of the densification process.